TRANSPARENCY OF BPI DANANTARA IN MANAGING THE DIVIDENDS OF STATE-OWNED ENTERPRISES - Zita Humairoh; Reka Dewantara; Amelia Sri Kusuma Dewi (Journal of International Islamic Law, Human Right and Public Policy, 2026)
The transformation of Indonesian State-Owned Enterprises (SOEs) through the establishment of the Danantara Investment Management Agency (BPI Danantara) marks a paradigm shift toward a Sovereign Wealth Fund (SWF) model. This research aims to analyze the transparency mechanisms of dividend management under the framework of Law No. 16 of 2025 concerning SOEs, specifically in mitigating the risk of "financial contagion" caused by high-debt strategic projects such as the Jakarta-Bandung High-Speed Railway (Whoosh). Using a normative legal research method with a case study approach, this study examines the legal protections provided by the new regulation against the improper use of dividends to bail out distressed entities. The results of this study indicate that Law No. 16/2025 establishes a "legal firewall" that separates state-separated assets for investment purposes from public service obligations. The study concludes that BPI Danantara’s commitment to allocating dividends solely for productive reinvestment is a crucial manifestation of fiduciary duty. Furthermore, the adoption of international reporting standards, such as the Santiago Principles, is essential to ensure that SOE profits are utilized for long-term national capital accumulation rather than as a non-transparent instrument for debt restructuring of inefficient projects.